Studi Eksperimental Water Filter Dust Collector untuk Meningkatkan Kualitas Udara di Dalam Bengkel Heat Treatment - Yohanes Nugroho; Bayu Prabandono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2019)
Heat treatment is a manufacturing process that aims to change the metal structure by heating it to reach the crystallization temperature (austenite), then holding it and cooling it (quenching) so that it reaches the desired characteristic goals. In the quenching process, it causes smoke-shaped air pollution which has no known pollutant content in it. This study aims to determine the content of pollutants in smoke in the process of quenching heat treatment, using an experimental method that uses a dust collector machine with a water filter model, by working the air during the quenching process sucked by a water filter dust collector, then passing the water filter, finally the pollutants are left in the water filter. Thus water contaminated by pollutants will be compared with pure water before being polluted. From the results of the research the quenching process produced sodium pollutants of 44.1%, magnesium 1.79%, aluminum 1.25%, barium 95 parts per million, plumbum 82 parts per million, copper 22 parts per million.